Pengembangan Membran Magnesol untuk Pemurnian Biodiesel - Saiful, Saiful; Nurfitriana, Nurfitriana; Ramli, Muliadi; Maulana, Ilham (Jurnal Rekayasa Kimia & Lingkungan, 2013)
Magnesol membrane has been prepared by mixing chitosan polymer with magnesol particles via phase inversion method. The optimum compositions of adsorptive membranes were 3% chitosan, 15% DMF and 60% loading adsorbent. The porosity of these membranes was 34,17% and swelling degree was 51,91%. The membrane clean water flux was 224,4 Lm2h1 at a transmembrane pressure of 2.5 bar. The adsorptive membrane possesses an open and interconnected porous structure with a large surface area available for biodiesel purities adsorption. The results showed that after contacting in 60 minutes, numbers of acid value was reduced as 81,12% which is in accordance with value of SNI quality standards. In addition, the soap content adsorbed was 86,74% as potassium soap and 86,73% as sodium soap. The regenerated membrane can be reused with mantaining the high adsorption capacity. The methanol was better than ethanol to regenerate the magnesol membrane. The Magnesol membrane will be a new alternative method for biodiesel purification.Keywords: biodiesel, membrane adsorption, chitosan, magnesol, acid number, soap